Insights into wind-driven heavy metal pollution and human health risk assessment in a typical lead-zinc mining area of northern China - Zun-zhuang Ke; Xue Han; Ran Zhou; Yi-fei Zhang; Guan-nan Liu; Chang-qing Zhang; Zhao Liu; Xiao-sai Li; Wen-bo Li (China Geology)
ABSTRACT: Long-term mining activities can result in the release of heavy metals into soil, ultimately posing a threat to human health. In arid and semi-arid regions, wind-driven transport of these toxic metals from mining areas represents a primary mechanism for their spatial distribution. To evaluate pollution levels and associated health risks of eight metals, A total of 95 soil samples, corresponding 25 vegetable samples and 3 tailing samples were collected from various land types surrounding a typical Pb-Zn mine in northern China’s semi-arid region. The mean concentrations of As, Cd, Cr, Cu, Hg, Ni, Pb and Zn in soils were 62.8, 0.27, 29.6, 11.5, 0.02, 14.4, 49.9 and 109.5 mg/kg, respectively. Among these, As, Cd, Pb, and Zn emerged as the predominant pollutants, with some samples exceeding national risk screening values. The results of contamination factor (CF), pollution load index (PLI) and geo-accumulation index (Igeo) indicated that heavy metals in most soils exhibited non-polluted level or slight pollution level, though localized severe contamination by As, Cd, Pb, and Zn was observed. Spatial distribution analysis demonstrated similar dispersion patterns for As, Cd, Pb, and Zn, with wind-mediated transport extending up to 2.0 km from contamination sources. Pearson’s correlation analysis and principal component analysis (PCA) suggested that As, Cd, Pb and Zn mainly originated from mining activities, and Cr, Ni, Cu and Hg derived from soil parent materials. All vegetable samples contained metal concentrations below food safety thresholds. Health risk assessment showed hazard quotient (HQ) values for individual metals below 1 across all exposure groups, indicating negligible non-carcinogenic risk. Similarly, carcinogenic risk (CR) values for As, Cd, Cr, and Pb fell within acceptable ranges. While mining activities have induced significant localized contamination, the overall affected area remains limited in arid and semi-arid regions. However, greater attention should be directed toward potential health implications from vegetable consumption in proximity to mining operations within arid and semi-arid regions.